The Evaluation of Teacher Performance in Higher Education - Joseph Morales (International Journal of Science and Society, 2022)
The purpose of this article is to present a critical review of the ways in which the performance of university teachers are usually evaluated. Generally, the institutions state proposal of evaluation that usually coincide with what is evaluated and the use of the results. It includes the review of the different evaluation models to show the discrepancies between the objectives and the practices, that is, the poor relationship between the model used and what is done. Universities usually declare that the focus of the evaluation is improvement of practice. One of the most used instruments is the questionnaire, with which an accurate measurement can be made, but generally it does not evaluate the teaching performance, but, in the best-case scenario, the opinion of the students. If universities state that the evaluation should serve to improve the teaching practice, it would be advisable to favor the constructivist model that promotes changes required through the reflection that arises from the review of the self-evaluation, the hetero-evaluation and the co- evaluation.